Arte é política, afeta e transforma: uma experiência de aprendizagem com as Crias do Curro Velho - FONSECA, Thalia Santos da (2023)
This research stands upon life's experiences in art with children and teenagers from Vila da Barca, through the Iniciação Científica (artistic iniciation) project from Curro Velho in Belém do Pará. In the research, which I am involved in, I put myself looking for understanding how the notion of affectionbility and fable are important, in the sense of modifying and creating new perspectives into realities inside the outskirts, therefore instigating a collective political movement. I emphasize how the trust, the journey and representativity of instructors is crucial while the work is being done through the months. I point in the trajectory of the research, how each element, which builds the theater concerts, is important to the children: costumes and the scenography. I talk about the mutual transformation between teacher and student and how art-education went through my personal and academic life.